\(a,x^2+2x+1=\left(x+1\right)^2\\ b,x^2-8x+16=\left(x-4\right)^2\\ c,\left(x^2+x+\dfrac{1}{4}\right)=x^2+2.\dfrac{1}{2}.x+\dfrac{1}{4}=\left(x+\dfrac{1}{2}\right)^2\\ d,x^2-4x+4=\left(x-2\right)^2\)
a) x2 + 2x + 1 = x2 + 2.x.1 + 12 = (x + 1)2
b) x2 - 8x + 16 = x2 - 2.x.4 + 42 = (x - 4)2
c) x2 + x + \(\dfrac{1}{4}\) = (x + 1/2)2
d) x2 - 4x + 4 = x2 - 2.x.2 + 22 = (x - 2)2
a) Bình phương 1 tổng :
`(x^2 + 2x + 1) = (x + 1)^2`
b) Bình phương 1 hiệu :
`(x^2 - 8x + 16) = (x +4)^2`
`c)`
`x^2 + x + 1/4`
`= x^2 + 2 . x . 1/2 + ( 1/2 )^2`
`= ( x + 1/2 )^2`
`d)`
`x^2 - 4x + 4`
`= x^2 - 2 . x . 2 + 2^2`
`= ( x - 2 )^2`
`*` Áp dụng:
`a^2 + 2ab + b^2 = ( a + b )^2`
`a^2 - 2ab + b^2 = ( a - b )^2`
\(a)x^2+2x+1=x^2+2.x.1+1^2=\left(x+1\right)^2\)
\(b)x^2-8x+16=x^2-2.x.4+4^2=\left(x-4\right)^2\)
\(c)x^2+x+\dfrac{1}{4}=x^2+2.x.\dfrac{1}{2}+\left(\dfrac{1}{2}\right)^2=\left(x+\dfrac{1}{2}\right)^2\)
\(d)x^2-4x+4=x^2-2.x.2+2^2=\left(x-2\right)^2\)